Potential Utilization of Oil Palm Mesocarp and Oil Palm Empty Fruit Bunch Fiber Powder as Natural coagulant-flocculant for POME Treatment - Mohd Atarabusyi, Muhammad Aiman; Abdullah, Nor Maizzaty; Arifin, Siti Nor Hidayah; Mohd Apandi, Najeeha; Ali, Muhammad Faiz Haikal (International Journal of Integrated Engineering, 2025)
The palm oil industry is one of the agro-based industries that has a high contribution to the global economy, including Malaysia. However, there is a negative impact on the environment caused by palm oil production, which results in high waste pollution known as palm oil mill effluent (POME). A common practice for the palm oil industry regarding the POME treatment is using conventional coagulant and flocculant agents due to their effectiveness and affordable cost. However, high usage of agents in wastewater treatment can threaten human and environmental health, such as air and soil pollution, water pollution, and disease transmission. The palm oil industry also produces other waste such as oil palm mesocarp (OPM) and oil palm empty fruit bunch (OPEFB) which have the potential to be utilized due to their existence of a hydroxyl group in cellulose and lignin. Therefore, this study provides a novel approach by utilizing naturally occurring functional groups in OPM-OPEFB to facilitate pollutant removal in POME as sustainable natural coagulants-flocculants. The effective treatment of POME is critical for reducing its environmental footprint, given the high organic content and large quantities generated by the palm oil industry. This study demonstrates the ability of these biopolymers to achieve significant reductions in turbidity and suspended solids, aligning with the principles of green chemistry. The effectiveness of lignocellulose biomass in enhancing coagulation-flocculation, offering a sustainability alternative to conventional chemical coagulants. For the coagulation-flocculation treatment of POME, jar tests were performed to evaluate the effectiveness of the process. The parameters measured for the untreated and treated POME are pH, dissolved oxygen (DO), turbidity (TUR), biochemical oxygen demand (BOD), total suspended solids (TSS), and ammoniacal nitrogen (AN). Removal efficiencies of pH, TUR, BOD, TSS, and AN were 7.39%, 41.28%, 53.14%, 62.69%, and 30.56% respectively for OPM-OPEFB. Results obtained from characterization show that the coagulation–flocculation mechanism was ruled by the existence of a hydroxyl group and hydrogen bond in cellulose and lignin that increase the rate of absorption and bonding. OPM-OPEFB demonstrates the potential to lower the organic contaminants. Therefore, optimizing contact time and coagulant dosage may enhance the effectiveness of the removal of organic pollutant in the POME.